Answer :

from the laws of exponents , we know that ,


=


And , am × an = a(m+n)


And , am ÷ an = a(m-n)


And , (am)n = a(mn)


So , we have × × 3-1 × = × 34 × ×


= × 34 × ×


= × 34 ×


= ×34×


=


=


=


=


=


× × 3-1 × =


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Express the produNCERT - Mathematics Exemplar

Simplify:

NCERT - Mathematics Exemplar

Out of the four oNCERT - Mathematics Exemplar

Out of the four oNCERT - Mathematics Exemplar

Express 16–2NCERT - Mathematics Exemplar

Express as a poweNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar